California Statutes and Amendments to Codes, 1895: With Notes of Decisions from Volumes 97 to 104, Inclusive, of California Reports (San Francisco, CA: Bancroft-Whitney, 1895), 63-64. Amendments to the Civil Code, Chapter 168—An Act to Amend Several Sections Relating to the National Guard of California, § 1942. In effect March 26, 1895 - (:unkn) unknown (General Publisher, 1895)
Prohibited militias to wear colors not associated with the United States. Prohibited any unorganized militia other than the regular organized National Guard in the state of California without a license from the governor. Violators guilty of a misdemeanor subject to arrest and punishment therefor.
--
Keywords: MILITIAS